An assessment on the occurrence of soil-transmitted helminths in the primary school pupils of San Joaquin Central School, Palo, Leyte - Miguel, Jabesse Esther C. (2013)
In the Philippines, one of the major neglected public health problem is soil-transmitted helminths (STH) infections. Studies have shown that the most susceptible age groups for this kind of infection are primary school pupils ranging from five to fourteen years old. STH infections can affect the physical development and mental health of children, thus an assessment of the prevalence of STH infection in primary schools is necessary. This study aimed to assess the occurrence of STH infection in the pupils of San Joaquin Central School, Palo, Leyte. The protocol of WHO on the diagnosis of intestinal parasites was adapted in this study. Stool samples from pupils in each grade level were collected and examined using the Kato-katz method to determine the presence of STH. Of the STH infections, only ascariasis and trichuriasis were observed in this study. The prevalence of infection was 30.39%. The results of this study revealed a notable number of Ascaris lumbricoides and Trichuris trichiura infected pupils in San Joaquin Central School.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.
Keywords: Helminths